Create uniqueness : how to turn a passion into a business - Pozzoli, Riccardo, ....-; Di Stefano, Vanessa, ....- (London : Kogan page, 2019)
"Create your dream job by turning your passion into a profitable business. The business world has completely changed. The old routes to building a successful organization have been entirely revolutionized. In a world which is being transformed with a speed that was unthinkable barely a generation ago, the doors have been thrown wide open to serial entrepreneurs, digital innovators and career reinventors. In Create Uniqueness, Riccardo Pozzoli, one of Italy's most successful entrepreneurs, and co-founder of the fashion phenomena The Blonde Salad, shares his story about creating a thriving business and building rewarding work environments. Create Uniqueness is a passionate yet practical guide to identifying a business idea, embracing new ways of working, thinking unusually and building a great company without losing sense of your original idea"--
Keywords: New business enterprises; Technological innovations -- Economic aspects; Venture capital